Fahr′s disease and psychiatric syndromes: A case series - Deepak Ghormode; Uma Maheshwari; Natasha Kate; Sandeep Grover (Industrial Psychiatry Journal, 2011)
Fahr′s disease is characterized by basal ganglia calcification with clinical manifestations in the form of neuropsychiatric disorders, neurological symptoms, and cognitive symptoms. In this case series, we describe two cases of basal ganglia calcification, one of whom presented with psychotic symptoms and the other with mood symptoms, and discuss the literature with regard to psychiatric manifestations of basal ganglia calcification.